Learning Global Citizenship Skills in a Democratic Setting: An Analysis of the Efficacy of a Moral Development Method Applied in China - Kang, Lei; Rubienska, Anne; Shaogang, Yang; Tie, Zheng; Ying, Qiu (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
To reduce the limitations of current measures of morality, and to focus on an effective approach to moral development among university students, the researchers adopted the Konstanz Method of Dilemma Discussion, to probe whether this type of method can also be applied among Chinese students, regarding the development of moral competence. ‘Moral Competence’, also known as ‘moral-democratic’ competence, is a concept developed by German psychologist, Professor Georg Lind. It is built upon the theories of Kohlberg, yet focuses on moral judgment and democratic decision-making competence. Lind designed a scale based on his dual-aspect theory, and suggested a follow-up method for building up moral competence. KMDD has been used in Germany and other countries for many years and has achieved positive results when applied. The initial application of this type of method in China started in 2012. After more than two years’ of planning and research, we used this method with different groups of Chineseuniversity students and tested its efficacy. Participants were set as the control and experiment groups. After analysing the preand- post-test data from all the participants, the result shows that the intervention effect with experiment groups was very significant with a noticeable Absolute Effect Size of C-score, while the competence score of control group regressed sharply due to reasons to be identified. Data from the experiment were analysed and intervention results were compared, to examine the efficacy of the method and to evaluate further application and research of KMDD in China.